Bread and Roses, and Quality Too? A New Faculty Majority Negotiating the New Academy. (3rd September 2017) - Rhoades, Gary
ABSTRACT: This study of 252 collective bargaining agreements examined language negotiated in "class cancellation fee" provisions addressing "just-in-time" employment of adjunct faculty. The analysis focused on the balance between managerial discretion and professional rights and on whether and how contract language addresses remuneration (bread) and respect (roses) as well as quality, which are at the heart of the contingent faculty labor movement's mantra about faculty's working conditions being students' learning conditions. Comparing the language in 64 bargaining units that cover only adjunct faculty to language in 188 units that combine part- and full-time faculty, and considering the language negotiated in Service Employees International Union "metro campaign" contracts, I found that provisions are both markers of precarious employment and of adjunct faculty's agency to countermobilize and improve the quality of their working conditions, particularly in part-time-only units and in the new metro campaigns, though not in terms of language explicitly invoking quality concerns.